Transformation into Platform - How can an organisation move from a single-sided business to platforms? A case study at Lyyti - Harmaa, Juho (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The research studies the transformation from a single-sided offering to a multi-sided platform. The study aims to define platforms and their benefits, creating a theoretical framework by applying change management models with the platform theory, and by finding critical change points of the transformation. The empirical research was done by utilizing action research. The researcher worked as project manager in the case company, and studied the transformation project by working actively and leading the project team. The result of the project was a study of how the company would be able to manage the transformation. The results clearly showed that the company didn’t have the capabilities to finish the transformation. As a conclusion, the study showed that the critical change points that led to the project failure were, that the project was managed with insufficient change managerial efforts, which later resulted as lack of commitment to re-allocating the resources to complete the transformation. Many of the critical change points were results of combined change managerial and platform-related issues.